2014
DOI: 10.1117/12.2038818
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and scattering of vector light beam in turbid scattering medium

Abstract: Due to its high sensitivity to subtle alterations in medium morphology the vector light beams have recently gained much attention in the area of photonics. This leads to development of a new non-invasive optical technique for tissue diagnostics. Conceptual design of the particular experimental systems requires careful selection of various technical parameters, including beam structure, polarization, coherence, wavelength of incident optical radiation, as well as an estimation of how the spatial and temporal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In contrast, studies examining the effect of increasing beam order on beam penetration through biological tissue have shown that increasing order improves beam penetration. In recent years, the connection between attenuation and OAM has been investigated in the context of biology and medicine 7,8,13,[19][20][21] . Studies that have used numerical methods that model this problem have shown that increasing the topological charge does improve permeability and increases the contrast of the outgoing beam [22][23][24] .…”
mentioning
confidence: 99%
“…In contrast, studies examining the effect of increasing beam order on beam penetration through biological tissue have shown that increasing order improves beam penetration. In recent years, the connection between attenuation and OAM has been investigated in the context of biology and medicine 7,8,13,[19][20][21] . Studies that have used numerical methods that model this problem have shown that increasing the topological charge does improve permeability and increases the contrast of the outgoing beam [22][23][24] .…”
mentioning
confidence: 99%